Compound posterior cruciate ligament and popliteal artery injury due to dog bite: A case report - Yashwant Singh Tanwar; Atin Jaiswal; Hitesh Lal; Ashok Rajput (Acta Orthopaedica et Traumatologica Turcica, 2017)
Injuries due to dog bites are a common occurrence and are mostly trivial. Severe dog bite injuries requiring hospitalization and complex reconstructive procedures are more common in children. We present the case of a five year old child with popliteal artery thrombosis and compound Posterior Cruciate ligament injury due to a dog bite. The child was managed by immediate thrombectomy, meticulous debridement and knee spanning external fixation followed by Skin Grafting. At one year post surgery range of motion was 10–110°, with no distal neurovascular deficit and no sign of instability. Keywords: Dog bite, PCL injury, Popliteal artery injury